SURVIVAL AND PROGRESSION AFTER RADICAL NEPHRECTOMY IN A COHORT OF NON-METASTATIC RENAL CELL CARCINOMA TREATED WITH CURATIVE INTENT - Khan, Nouman; Khalil, Muhammad Arshad Irshad; Ali, Azfar; Manzoor, Sidra; Urooj, Namra; Mir, Khurram (Journal of Ayub Medical College Abbottabad, 2019)
Background: Radical nephrectomy (RN) is a standard treatment of cure for non-metastatic renal cell carcinoma (NMRCC). Long-term outcome data are limited for Pakistani population. Our aim was to assess the long-term outcomes of RCC treated with curative intent with radical nephrectomy (RN) and to study the 5 & 10years survival outcomes in patients with NMRCC who underwent radical nephrectomy. Methods: This is a retrospective review and analysis of the data between December 2006 and February 2017. We included all the adult patients (age ‰¥18 years) with NMRCC from both genders irrespective of their histologic subtypes who underwent radical nephrectomy (RN) with a curative intent. The data was analysed for overall survival and recurrence rates at 5- and 10-years using Kaplan-Meier survival analysis. Multivariate analysis was performed using Cox-regression to identify risk factors associated with poor overall outcome in terms of recurrence and mortality. Results: Three hundred and forty-four patients with 195 (55.5%) males and 149 (44.2%) females with a mean age of 53.5±14.1 years were monitored for a mean follow-up of 31.1±26.77 months (range: 3-132 months). Overall there were 46 (13.4%) deaths. Forty-nine 14.2%) cases had disease recurrence with 33 (9.5%) deaths from disease progression. The 5-year progression-free survival was 37% (95% CI: 49.04-72.76) with the median time to recurrence of 33 months (95% CI: 27.6-38.4) and the median overall survival was 103.7 months (95% CI: 95.7-111.7). The 5-year overall survival was 76.1% (95% CI: 75.2-77) while 10-year survival was 70.8%. There was a significant median survival difference for cases with and without recurrence (log-rank Ï‡2: 117.5, p<0.001), T stage, Fuhrman's grade, and early postoperative recurrence. Conclusion: Radical nephrectomy offers the best survival for non-metastatic renal cell carcinoma patients with excellent postoperative survival and progression-free profile. Although renal cell cancer presents in younger age group but the long-term survival after radical nephrectomy in Pakistani population is similar to the rest of the world. Keywords: renal cell carcinoma; radical nephrectomy; recurrence; survival